A STUDY OF THE IMPACT OF THE INTERNET ON THE SOCIALIZATION OF TEENAGERS IN URBAN AREAS - Pankaj Raman (International Journal of Multidisciplinary Research and Studies, 2021)
This thesis will explore the influence of urbanisation and modernity on the structure of families in the city of Muscat. Muscat is the capital of the Sultanate of Oman, and this thesis will focus on the city. Both Meadows and Danesh note out that urbanisation and industrialization have contributed, at least in part, to changes in Oman's family structures and the functions that members play within those structures. It is projected that the patterns of family structure would reflect more "modern" features than the norms and goals of family life will. This is because of the following: This is what should be expected. The following are the top three most significant concerns: to determine family size (fertility), and child care patterns, especially with mothers working to meet modern economic needs; and to determine the upcoming question of the elderly: is it still the responsibility of the children to provide care, or is it the responsibility of the government, or is it both? Even as late as 20 years ago, Oman was still classified as a "Third World" nation. Oman is a contemporary nation that just recently embarked on its modernization journey, both in terms of its economic and social development. Many people believe that during the course of the last 20 years, Oman has been one of the nations that has been increasing at one of the rates that is among the fastest. The new contemporary government of Oman, which is led by His Majesty Sultan Qaboos bin Said, had to start with institutions that were built on historical practices while having very little resources to deal with. This is one of the reasons why this is the case. Since then, the expansion that has taken place in a number of different economic sectors, most notably the oil industry, has made it possible for the government of Oman to develop its historic cities and capital, in addition to constructing new modern communities. This is the case even though oil production has remained relatively stable. Infrastructural projects have also been given a high priority, and this includes the development of highways, ports (both sea and air), modern hospitals, and schools.